The MultiGradeMultiLevel-Methodology and Its Global Significance : Ladders of Learning - Scientific Horizons - Teacher Education. - Müller, Thomas (Prolog - Theorie und Praxis der Schulpädagogik Ser., 2015)
The MultiGradeMultiLevel-Methodology (MGML) offers students and teachers a reliable learning framework for both individualized and community-oriented education. With "ladders of learning" guiding children through their tasks, MGML allows mixed-age groups to work together in one classroom (multigrade) at various achievement levels (multi-level) according to a defined curriculum. MGML allows teachers to spend less time teaching and more time supporting their students individually and working with them personally. In this publication the authors introduce MGML's origin and international variations localizing them within scientific horizons. As a core result MGML's significance stretches far beyond individual processes or single classrooms no matter if the school is in Germany or in Kenya, if the students are at primary or at university level. MGML has shown its potential to impact not only schools and students, but the global community.